Bacillus subtilis HelD, an RNA Polymerase Interacting Helicase, Forms Amyloid-Like Fibrils - Kaur, Gundeep; Kapoor, Srajan; Thakur, Krishan G. (Frontiers in Microbiology, 2018)
HelD, an RNA polymerase binding protein from Bacillus subtilis, stimulates transcription and helps in timely adaptation of cells under diverse environmental conditions. At present, no structural information is available for HelD. In the current study, we performed size exclusion chromatography coupled to small angle X-ray scattering (SEC-SAXS) which suggests that HelD is predominantly monomeric and globular in solution. Using combination of size exclusion chromatography and analytical ultracentrifugation, we also show that HelD has a tendency to form higher order oligomers in solution. CD experiments suggest that HelD has both α-helical (~35%) and β sheet (~26%) secondary structural elements. Thermal melting experiments suggest that even at 90 C, there is only about 30% loss in secondary structural contents with Tm of 44 C. However, with the increase in temperature, there was a gain in the β-sheet content and significant irreversible loss of α-helical content. Using a combination of X-ray fiber diffraction analysis, and dye based assays including Thioflavin-T based fluorescence and Congo red binding assays, we discovered that HelD forms amyloid-like fibrils at physiologically relevant conditions in vitro. Using confocal imaging, we further show that HelD forms amyloid inclusions in E. coli. Bioinformatics-based sequence analysis performed using three independent web-based servers suggests that HelD has more than 20 hot-spots spread across the sequence that may aid the formation of amyloid-like fibrils. This discovery adds one more member to the growing list of amyloid or amyloid-like fibril forming cytosolic proteins in bacteria. Future studies aimed at resolving the function of amyloid-like fibrils or amyloid inclusions may help better understand their role, if any, in the bacterial physiology.